2020
DOI: 10.1089/ct.2020;32.83-85
|View full text |Cite
|
Sign up to set email alerts
|

Financial Toxicity Is Associated with Poorer Quality of Life in Thyroid Cancer Survivors

Abstract: Background More than 50,000 Americans are diagnosed with thyroid cancer each year (1). Owing to excellent survival rates, with a 5-year survival rate reaching 98%, it is estimated that more than 750,000 thyroid cancer survivors are living in the United States (1,2). In view of the fact that thyroid cancer mostly affects younger individuals, the majority of thyroid cancer patients are working-age adults who do not yet qualify for government health insurance benefits. Prior studies have indicated that thyroid ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Several studies have reported an association between socioeconomic factors and anxiety, depression, or QoL in TC patients ( Tables 1 – 3 ) [ 14 , 19 , 23 , 25 , 28 , 33 - 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have reported an association between socioeconomic factors and anxiety, depression, or QoL in TC patients ( Tables 1 – 3 ) [ 14 , 19 , 23 , 25 , 28 , 33 - 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Financial strain and employment status have also been associated with anxiety, depression, or QoL in TC [ 15 , 24 , 26 , 28 , 35 , 44 , 47 - 50 ]. Financial difficulties were reported in 43% of TC survivors, leading to higher levels of anxiety and depression, lost productivity, and an inability to change jobs [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations